Development of a performance measurement system for manufacturing systems (2008)
Taylor and Davis total productivity model has significant advantage over the traditional and more commonly used productivity models - its holistic nature. The model incorporates elements of net sales, inventory changes, wages and salary, investor's contribution, working and fixed capital. This paper presents a unique approach in the determination of the total factor productivity for a manufacturing organisation. This study is motivated by the dearth of models comprehensive enough to cover the major aspects of business apart from the usual input-output approach of productivity analysis which is limited to the output items and material/non-material resources. The results obtained clearly demonstrate the feasibility of applying Lagrange multiplier in optimising the variables and parameters of the model. The research has implications for decision making in several dimensions primarily it aids the utilisation of optimal solutions in arriving at decisions. This would avoid suboptimal decision making and promotes implementation of optimal decisions. This study is new, in that, it presents an enhanced version of a model that has been available to researchers several years back.